Glycemic index and fiber content of wholemeal bread enriched with Bambara groundnut (Vigna subterranea L. Verdc) - Nufaisah Afifah; Rimbawan Rimbawan; Nasution Zuraidah (BIO Web of Conferences)
Foods rich in dietary fiber may have a lower glycemic index (GI). The use of whole wheat and Bambara groundnuts in wholemeal bread production enhances its fiber content, offering significant dietary benefits. Wheat has a dietary fibre content of 11.6-17 g/100 g, and based on the Indonesian food composition table, dried Bambara groundnuts have a fiber content of 26.3 g/100. This experimental study compares the glycemic index of wholemeal bread made from 100% whole wheat flour (WW) with wholemeal bread made from 80% whole wheat flour and 20% Bambara groundnut flour (WB). The result showed that both breads had high total dietary fiber (TDF) content (WW: 6.1 g/100g and WB: 6.9 g/100 g), as well as medium glycemic index values (WW: 55.1 and WB: 61.1). This study suggests that Bambara groundnut has the potential as ingredients for producing high-fiber food products.